(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
This work aims to analyze how international accreditations are developed in the professional field of computing based on learning outcomes selected by academics and professionals from different countries in the field of computing. Methodology: The data used in this study have been obtained from the evaluations carried out by the National Agency for Quality Assessment and Accreditation (ANECA) in Spain, Argentina and Mexico between January 2014 and July 2020 and from those that are ongoing in the time of closing the article. Also, the information obtained in the meta evaluation carried out annually to the SIC Program has been analyzed. Results and conclusions: 26 universities have obtained the Euro-Inf label for their computer science degrees / educational programs in the period analyzed. Since 2020 the evaluation has been carried out virtually in its entirety, due to the pandemic caused by COVID-19.